2011
DOI: 10.5301/jn.2011.6458
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of glomerular VEGF-NO axis in diabetic rats: prevention by chronic therapy with propyl gallate

Abstract: The imbalance of the VEGF-NO axis in the glomeruli of diabetic rats may have resulted from eNOS inactivation, but not from the decrement in eNOS expressions at the early stage of rat diabetic nephropathy. Propyl gallate improved glomerular pathological changes in diabetic rats, possibly through oxidative stress reduction and VEGF-NO axis recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The uncoupling of the VEGF-NO • axis in the glomeruli resulting from eNOS inactivation has been reported in glomerular endothelial dysfunction (182) . Tian et al (145) confirmed the improvement of glomerular pathological changes in diabetic rats through oxidative stress reduction and VEGF-NO • axis recovery and prevention of glomerular endothelial dysfunction by propyl gallate.…”
Section: Polyphenols In the Amelioration Of Endothelial Dysfunctionmentioning
confidence: 91%
See 1 more Smart Citation
“…The uncoupling of the VEGF-NO • axis in the glomeruli resulting from eNOS inactivation has been reported in glomerular endothelial dysfunction (182) . Tian et al (145) confirmed the improvement of glomerular pathological changes in diabetic rats through oxidative stress reduction and VEGF-NO • axis recovery and prevention of glomerular endothelial dysfunction by propyl gallate.…”
Section: Polyphenols In the Amelioration Of Endothelial Dysfunctionmentioning
confidence: 91%
“…Gallic acid, a trihydroxy benzoic acid, restored eNOS activity in glomerular endothelial cells of diabetic rats through oxidative stress reduction in diabetic nephropathy ( 144 , 145 ) . Daidzein, a phyto-oestrogen, reversed changes in vascular reactivity through NO ∙ and PG-related pathways, and attenuated oxidative stress in aortic tissue of diabetic rats ( 146 ) .…”
Section: Polyphenols In the Amelioration Of Endothelial Dysfunctionmentioning
confidence: 99%
“…Diabetic nephropathy is one of the leading causes of end-stage renal failure (1). The inactivation of endothelial nitric oxide synthase (eNOS) has been considered to be a recently discovered mechanism of diabetic nephropathy (2,3), which severely impairs glomerular endothelial cell nitric oxide (NO) production and causes glomerular endothelial cell dysfunction, which are impairments that contribute to the development of diabetic nephropathy (2,4). However, the specific mechanism that causes eNOS inactivation remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Human glucagon-like peptide-1 (GLP-1) analogues, such as liraglutide, have been demonstrated to elicit protective effects in diabetic vascular complications (4), thus suggesting that liraglutide exhibits an endothelial cell function. Other investigations have also demonstrated that the protective effect Liraglutide ameliorates renal injury in streptozotocin-induced diabetic rats by activating endothelial nitric oxide synthase activity via the downregulation of the nuclear factor-κB pathway of liraglutide on vascular systems involves the reduction of chronic inflammation (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high expression of VEGF is a common phenomenon in diabetic nephropathy [5], the factors related to NO deficiency are the most concerned for endothelial cell proliferation. Our recent studies have shown that oxidative stress may implicated to glomerular NO deficiency through inhibiting eNOS activity, and an antioxidant agent—propyl gallate—can restore eNOS activity [10]. However, whether propyl gallate can inhibit the proliferation of endothelial cells and arrest the progression of diabetic nephropathy is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%